The feasibility and acceptability of self-sampling and HPV testing using Cepheid Xpert® HPV in a busy primary care facility - Y.L. Woo (Elsevier, 2019)
Malaysia's approach to reducing the burden of HPV-related disease has centred on adolescent vaccination and cervical screening with Pap smears. While the vaccination programme has been broadly successful, Pap smear screening has been less successful. In an effort to improve screening uptake, the ROSE 1.0 pilot aimed to create more efficient screening, with improved quality and lower total cost.